First-in-Human Evaluation of the Safety and Efficacy of a Novel Stent Positioning Assistance System for Precise Positioning of Coronary Stents - Elias Hellou; Michael Jonas; Danny Dvir (Journal of Interventional Cardiology)
Objectives. This study was planned for evaluating the safety and efficacy of SPAS (stent positioning assistance system) device in first-in-human procedures. Background. SPAS is a novel device that can be used for improved positioning of coronary stents. Methods. Consecutive patients underwent percutaneous coronary intervention (PCI) with the SPAS device. Device-related adverse and serious adverse events were evaluated in addition to a dedicated questionnaire completed by operators immediately after using SPAS. Results. The SPAS device was deployed in 55 PCI procedures, comprising of heavily calcified lesions (33.3%), totally occluded (7.4%), and severely tortuous vessels (7.4%). In these procedures, nonbifurcation and nonostial (53.7%), bifurcation (22.2%), and edge-to-edge (24.1%) stenting techniques were employed. Analysis of the pooled scores for the five satisfaction-related questions gave an average score of 5.6 ± 1.5, with 40 (75.5%) operators providing an average satisfaction grade of >5; the average operator-rated SPAS device accuracy performance scores exceeded 6 out of 7 (on visual analog score). The time spent for positioning the stent with the SPAS device averaged 41 ± 68.0 seconds. The SPAS device was rated as easy to use (6.1 ± 1.6) and reliable (6.1 ± 1.7). No device-related adverse events were reported. Conclusion. This stent positioning device was evaluated in a consecutive cohort of standard and complex PCI procedures. The device was shown to be safe, easy, and precise to use, both in standard and complex cases.